Elimination study of the chemotherapy drug tamoxifen by different advanced oxidation processes: Transformation products and toxicity assessment. (February 2017) - Ferrando-Climent, Laura; Gonzalez-Olmos, Rafael; Anfruns, Alba; Aymerich, Ignasi; Corominas, Lluis; Barceló, Damià; Rodriguez-Mozaz, Sara
Abstract: Tamoxifen is a chemotherapy drug considered as recalcitrant contaminant (with low biodegradability in conventional activated sludge wastewater treatment), bioaccumulative, ubiquitous, and potentially hazardous for the environment. This work studies the removal of Tamoxifen from water by advanced oxidation processes, paying special attention to the formation of transformation products (TPs) and to the evolution of toxicity (using the Microtox ® bioassay) during the oxidation processes. Five types of treatments were evaluated combining different technologies based on ozone, hydrogen peroxide and UV radiation: i) O3, ii) O3 /UV, iii) O3 /H2 O2 (peroxone), iv) UV and v) UV/H2 O2 . Complete removal of tamoxifen was achieved after 30 min for all the treatments carried out with O3 while a residual concentration (about 10% of initial one) was observed in the treatments based on UV and UV/H2 O2 after 4 h of reaction. Eight TPs were tentatively identified and one (non-ionizable molecule) was suspected to be present by using ultra high performance liquid chromatography coupled to high resolution mass spectrometry. An increase of toxicity was observed during all the oxidation processes. In the case of ozone-based treatments that increase was attributed to the presence of some of the TPs identified, whereas in the case of UV-based treatments there was no clear correlation between toxicity and the identified TPs. Highlights: Complete removal of tamoxifen in all the AOP studied. 8 TPs were tentatively identified for the first time. Drastic increase of toxicity along all the experiments. At least one non-ionizable molecule was suspected to be present. Toxicity is due to the presence of TPs.